Sleep Quality After Intradialytic Oral Nutrition: A New Benefit of This Anabolic Strategy? A Pilot Study - González-Ortiz, Ailema; Ramos-Acevedo, Samuel; Santiago-Ayala, Victoria; Gaytan, Gabriela; Valencia-Flores, Matilde; Correa-Rotter, Ricardo; Carrero, Juan Jesus; Xu, Hong; Espinosa-Cuevas, Ángeles (Frontiers in Nutrition, 2022)
Background. Since disturbances of appetite and sleep are closely related and both affect metabolic disorders, it would be expected that a renal specific oral nutritional supplement (RS-ONS) that covers the energy the patient does not consume on the HD day, could contribute to improve the nutritional status and body composition, as well as sleep quality. There is still scarce information related to this topic. Aim. To evaluate the effect of the use of intra-dialytic RS-ONS vs RS-ONS at home on sleep quality, nutritional status, and body composition in patients on HD. Methods: Adult patients < 65 years, with ≥ three months on HD were invited to participate in an open randomized pilot study (ISRCTN 33897). Patients were randomized to a dialysis-specific high-protein supplement provided during the HD session (Intradialytic oral nutrition [ION]) or at home (control), during non-HD days (thrice weekly, for both) 12 weeks. The primary outcome was sleep quality defined by the Pittsburgh Sleep Quality Index (PSQI) score. Nutritional assessment included Malnutrition Inflammation Score (MIS), bioelectrical impedance analysis, anthropometry, 3-day food records, and routine blood chemistries. Results. A total of 23 patients completed the study. Age was median 37 (range 24 to 48 years), 42% were women. At baseline, the PSQI score was median 4 (range 2 to 7), and MIS was median of 6 (range 5 to 8); there were no baseline differences between groups. After intervention, both groups improved their MIS scores and similarly when we analyzed the whole cohort (pre- Vs. post-intervention P < 0.05). Patients in the ION group improved the overall PSQI score to median 3 (2 to 5), and assessment of sleep duration and sleep disturbances (pre- vs post-intervention P values < 0.05), with a trend towards an effect difference compared to patients consuming the supplement at home (P for treatment-effect across arms 0.07 for PSQI score and 0.05 for sleep latency). Conclusion: Oral supplementation improved nutritional status in the whole cohort, but only ION improved the PSQI score. More studies are needed to explore the nutritional strategies that influence the relationship between sleep and nutritional status in HD patients.